The Effect of Spandex Yarn on Structural Parameters and Elasticity of Polyamide-Spandex Knitted Fabric - Vu, Thi Hong Khanh; Bui, Thi Minh Thuy (Old Journal, 2018)
This study used three types of knitted fabric, which have similar knitted structure and differ in use of yarns. Each fabric used two types of yarn, the first one being the same for three fabrics, the second one is different. The first yarn was wound yarn, it was composed of one PA texture multi-filament yarn and one covered yarn (the core component is spandex monofilament; the covered component is composed of PA texture multi-filament yarn). The second yarn is spandex mono-filament yarn, it was different for three fabrics. This research was studied the effect of spandex content of fabric, fineness and structure of spandex yarn on the structural parameters and elasticity of fabrics. The tests to determine the structural parameters and elasticity of fabrics were carried out according to the Vietnamese or international standard methods. The results of the study showed that the fineness of spandex yarn (second yarn) is the important factor that could effect on the elasticity of fabric.